The effects of repetitive transcranial magnetic stimulation on empathy: a systematic review and meta-analysis - Yang, Cheng-Chang; Khalifa, Najat; Völlm, Birgit (Cambridge University Press, 2017)
Empathy is a multi-dimensional concept with affective and cognitive components, the latter often referred to as Theory of Mind (ToM). Impaired empathy is prevalent in people with neuropsychiatric disorders, such as personality disorder, psychopathy, and schizophrenia, highlighting the need to develop therapeutic interventions to address this. Repetitive transcranial magnetic stimulation (rTMS), a non-invasive therapeutic technique that has been effective in treating various neuropsychiatric conditions, can be potentially used to modulate empathy. To our knowledge, no systematic reviews or meta-analyses in this field have been conducted. The aim of the current study was to review the literature on the use of rTMS to modulate empathy in adults. Seven electronic databases (AMED, Cochrane library, Embase, Medline, Pubmed, PsycInfo, and Web of Science) were searched using appropriate search terms. Twenty-two studies were identified, all bar one study involved interventions in healthy rather than clinical populations, and 18 of them, providing results for 24 trials, were included in the meta-analyses. Results showed an overall small, but statistically significant, effect in favour of active rTMS in healthy individuals. Differential effects across cognitive and affective ToM were evident. Subgroup analyses for cognitive ToM revealed significant effect sizes on excitatory rTMS, offline paradigms, and non-randomised design trials. Subgroup analyses for affective ToM revealed significant effect sizes on excitatory rTMS, offline paradigms, and non-randomised design trials. Meta-regression revealed no significant sources of heterogeneity. In conclusion, rTMS may have discernible effects on different components of empathy. Further research is required to examine the effects of rTMS on empathy in clinical and non-clinical populations, using appropriate empathy tasks and rTMS protocols.